Adherence to the Vegetable-Fruit-Soy Dietary Pattern, a Reference From Mediterranean Diet, Protects Against Postmenopausal Breast Cancer Among Chinese Women - Cao, Shang; Liu, Linchen; Zhu, Qianrang; Zhu, Zheng; Zhou, Jinyi; Wei, Pingmin; Wu, Ming (Frontiers in Nutrition, 2022)
Background: The diet-center hypothesis has gained much support from the apparent protective effect of the Mediterranean diet on breast cancer. However, the evidence of the association between Mediterranean diet adherence and breast cancer molecular subtypes remains small, especially in non-Mediterranean populations. Methods: The subjects from the Chinese Wuxi Exposure and Breast Cancer Study, a population-based case-control study that included 818 patients and 935 healthy controls. A validated FFQ used for diet assessment and a modified version of the alternate Mediterranean Diet Score (aMED) which called the alternate Chinese Diet Score (aCHD) was developed to assess adherence to a migrated Chinese version of the Mediterranean diet, which we called the vegetable-fruit-soy dietary pattern. Soy foods, rapeseed oil and coarse cereals replaced legumes, olive oil and whole grains reflecting the cuisine of the region. We examined the association between the vegetable-fruit-soy diet adherence and breast cancer risk, and stratified by menopause status (pre-or post-menopausal) and receptor status (estrogen-receptor (ER), progesterone-receptor (PR) status and human epidermal growth factor 2 (HER2) oncogene expression, followed by 5 specific combinations (ER+, ER–, ER+/PR+, ER–/PR– and ER–/PR–/HER2–). Results: The results suggest the vegetable-fruit-soy dietary pattern was inversely associated with postmenopausal breast cancer risk (4th vs.1st quartile, OR for 0.57, 95%CI=0.41, 0.80; P-trend<0.001), and that the inverse association was somewhat stronger detect among ER- subtypes (OR=0.63; 95% CI=0.37, 0.94; P-trend = 0.003), as well as ER–/PR–subtypes (OR=0.64; 95% CI=0.41, 0.93; P-trend = 0.012). We did not observe any significant association between the vegetable-fruit-soy diet characteristics and ER+ subtype, as well as PR+ and ER+/PR+ subtypes. Conclusion: The favorable influence from the Mediterranean diet may also apply to Chinese women, the vegetable-fruit-soy dietary pattern may reduce the risk of postmenopausal breast cancer, particularly among ER- subtype, as well as ER–/PR–subtype.